Earned Media and Public Engagement With CDC's "Tips From Former Smokers" Campaign: An Analysis of Online News and Blog Coverage - Kornfield, Rachel; Smith, Katherine Clegg; Szczypka, Glen; Vera, Lisa; Emery, Sherry (JMIR Publications, 2015)
BackgroundIn March 2012, the US Centers for Disease Control and Prevention (CDC) launched the first-ever paid national tobacco education campaign. At a cost of US $54 million, "Tips from Former Smokers" (Tips) ran for 3 months across multiple media, depicting the suffering experienced by smokers and their families in graphic detail. The potential impact and reach of the Tips campaign was not limited to that achieved through paid media placements. It was also potentially extended through "earned media", including news and blog coverage of the campaign. Such coverage can shape public understanding of and facilitate public engagement with key health issues. ObjectiveTo better understand the contribution of earned media to the public's engagement with health issues in the current news media environment, we examined the online "earned media" and public engagement generated by one national public health campaign. MethodsWe constructed a purposive sample of online media coverage of the CDC's 2012 Tips from Former Smokers television campaign, focusing on 14 influential and politically diverse US news outlets and policy-focused blogs. We identified relevant content by combining campaign and website-specific keywords for 4 months around the campaign release. Each story was coded for content, inclusion of multimedia, and measures of audience engagement. ResultsThe search yielded 36 stories mentioning Tips, of which 27 were focused on the campaign. Story content between pieces was strikingly similar, with most stories highlighting the same points about the campaign's content, cost, and potential impact. We saw notable evidence of audience engagement; stories focused on Tips generated 9547 comments, 8891 Facebook "likes", 1027 tweets, and 505 story URL shares on Facebook. Audience engagement varied by story and site, as did the valence and relevance of associated audience comments. Comments were most oppositional on CNN and most supportive on Yahoo. Comment coding revealed approximately equal levels of opposition and support overall. We identified four common arguments among oppositional comments: government intrusion on personal behaviors, problematic allocation of governmental spending, questionable science, and challenges regarding campaign efficacy. Supportive comments tended to convey personal stories and emotions. ConclusionsThe Tips campaign received limited coverage on either online news or blog sources, but the limited number of stories generated engagement among online audiences. In addition to the content and volume of blog and news coverage, audience comments and websites' mechanisms for sharing stories via social media are likely to determine the influence of online earned media. In order to facilitate meaningful evaluation of public health campaigns within the rapidly advancing media environment, there is a need for the public health community to build consensus regarding collection and assessment of engagement data.